Advanced Information Systems Engineering Workshops CAiSE 2014 International Workshops, Thessaloniki, Greece, June 16-20, 2014, Proceedings - Iliadis, Lazaros; Papazoglou, Michael; Pohl, Klaus (Lecture Notes in Business Information Processing, 2014)
This book constitutes the thoroughly refereed proceedings of five international workshops held in Thessaloniki, Greece, in conjunction with the 26th International Conference on Advanced Information Systems Engineering, CAiSE 2014, in June 2014. The 24 full and eight short papers were carefully selected from 63 submissions. The five workshops were the First International Workshop on Advanced Probability and Statistics in Information Systems (APSIS), the First International Workshop on Advances in Services Design Based on the Notion of Capability, the Second International Workshop on Cognitive Aspects of Information Systems Engineering (COGNISE), the Third Workshop on New Generation Enterprise and Business Innovation Systems (NGEBIS), and the 4th International Workshop on Information Systems Security Engineering (WISSE).